Groundwater Identification Using the Resistivity Method to Improve Community Livelihoods in Bernung Village, Gedong Tataan District, Pesawaran, Lampung - Ordas Dewanto; Akhmad Dzakwan; Ilham Dani; Nasir Muhammad (CV Media Inti Teknologi, 2026)
Background: Water availability is a critical factor influencing the sustainability of community-based economic activities, particularly in fisheries and plantation sectors. In Bernung Village, Gedong Tataan District, Pesawaran Regency, limited water supply during the dry season has restricted the optimal utilization of fish ponds and plantation land, thereby affecting local economic productivity.Objectives: This study aims to describe a community service program integrating geoelectrical groundwater identification with community-based economic empowerment to support sustainable local business development.Methods: The program applied a Participatory Rural Appraisal (PRA) approach involving community participation throughout field surveys, groundwater-source identification, site selection, mentoring, and evaluation stages. Groundwater investigation was conducted using 1D geoelectrical sounding with a Schlumberger configuration at two observation points. The acquired data were interpreted to identify aquifer characteristics and to support groundwater utilization planning.Results: The geoelectrical survey identified potential aquifer zones at depths of 33.4–81.9 m at Point 1 and 21.5–82.8 m at Point 2, providing a technical basis for groundwater utilization planning. The program further supported the development of plantation land and fish-farming activities while improving community understanding of water-resource management and business development.Conclusion: The findings demonstrate that geoelectrical investigation serves not only as an effective groundwater exploration tool but also as a practical decision-support approach for strengthening community livelihoods and promoting more sustainable fisheries and plantation-based economic activities.